2013
DOI: 10.1111/j.1540-6288.2012.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Financial Sectors’ CDS Spreads and Other Gauges of Risk: Did the Great Recession Change Them?

Abstract: The objectives are to discern how the three financial sectors' credit default swap (CDS) spreads interrelate to each other and with three other risks in terms of possible contagion, competition, interdependence and independence relations under the full sample and two subperiods: the 2007 Great Recession and the 2009 Recovery, and to assess the impact of QE1 on those risks in the second subperiod. The results indicate that the own and cross-effects among the CDSs and the other risk measures are significant and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
5
1
Order By: Relevance
“…Although some studies (e.g. Doshi et al, 2013;Hammoudeh et al, 2013;Norden and Weber, 2009) showed certain systematic factors for CDS spreads that are endogenously embedded in the stock and bond markets of the underlying firms, we find that, at the time of writing, no previous study provides a comprehensive analyses on CDS systematic factors at entity level.…”
Section: Introductioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Although some studies (e.g. Doshi et al, 2013;Hammoudeh et al, 2013;Norden and Weber, 2009) showed certain systematic factors for CDS spreads that are endogenously embedded in the stock and bond markets of the underlying firms, we find that, at the time of writing, no previous study provides a comprehensive analyses on CDS systematic factors at entity level.…”
Section: Introductioncontrasting
confidence: 62%
“…Similarly, Norden and Weber (2009) find that stock market more often leads bond and CDS markets, but CDS provides more information for price discovery; in addition, Alexander and Kaeck (2008) further show that the connection between these financial markets are time-varying. Hammoudeh et al (2013) find that CDSs in financial sector affect CDSs in other sectors during the financial crisis, making the CDS market less stable.…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies have investigated the dynamic movements in credit default spreads (e.g., Longstaff et al, 2005, Berndt et al, 2008, Raunig and Scheicher, 2009, Zhang et al, 2009, Hammoudeh et al, 2013and Hammoudeh et al, 2013. For example, Hammoudeh, Nandha and Yuan (2013) examine the movements of the CDS indices for the three financial-sectors, banking, financial services and insurance in the short-and long-run over the period [2004][2005][2006][2007][2008][2009] and find that the individual dynamic adjustments to the equilibrium are different for those sectors.Other studies examine the CDS spreads as pure measures of credit risk (e.g., Bharath and Shumway, 2008, Blanco et al, 2005, Ericsson et al, 2006and Ericsson et al, 2009 or analyze the relationships between equity, bond and credit markets using time series instead of cross-sectional data (e.g., Bystrom, 2006, Zhu, 2006, Fung et al, 2008, Forte and Lovreta, 2009, Norden and Weber, 2009and Srivastava et al, 2016.…”
Section: Related Literaturementioning
confidence: 99%
“…Asymmetry and structural breaks (e.g., major credit events, bankruptcy) are forms of nonlinearities and are related to the CDS series (Galil, Shapir, Amiram, & Ben-Zion, 2014). Additionally, Hammoudeh, Bhar and Liu (2013) and Hammoudeh, Nandha et al (2013) varying effects of the risk free rate, leverage, equity volatility, bid-ask spread, term structure slope, swap spread, corporate bond spread, market return and market volatility on the changes in the CDS spreads for 32 Euro-area banks. Differently, we consider the sector CDS index spreads of three indices namely banking, financial and insurance sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Although a few studies (e.g., Doshi et al, 2013; Hammoudeh et al, 2013; Norden & Weber, 2009) have identified certain systematic factors for CDS spreads that are endogenously embedded in the stock and bond markets of the underlying firms, they did not provide a comprehensive analysis on CDS systematic factors at the entity level. In this study, we fill the gap in this strand of literature by providing a thorough investigation into the importance of systematic determinants of CDS spreads.…”
Section: Introductionmentioning
confidence: 99%